COVID-19 Is Distinct From SARS-CoV-2-Negative Community-Acquired Pneumonia - Zhou, Yutian; Guo, Shujin; He, Ye; Zuo, Qiunan; Liu, Danju; Xiao, Meng; Fan, Jinxiu; Li, Xiaohui (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Corona virus disease (COVID-19) is an infectious respiratory disease that has spread rapidly across the world. Many studies have already evaluated the clinical features of COVID-19, but how it compares with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-negative community-acquired pneumonia (SN-CAP) is still unclear. Moreover, COVID-19 mortality is correlated with disease severity, but indicators for severity grading have not been specified. We aimed to analyze the clinical characteristics of COVID-19 in comparison with SN-CAP and find indicators for disease severity in COVID-19. Methods: Patients diagnosed with COVID-19 and SN-CAP were enrolled. Clinical, radiological, and laboratory data were analyzed. Results: The numbers of COVID-19 and SN-CAP patients enrolled were 304 and 138, respectively. The age of the patients was not significantly different between the groups. Compared with SN-CAP, COVID-19 patients had more symptoms of fever and dyspnea; and showed significant difference in blood count results. Computed tomography (CT) imaging of COVID-19 patients showed patchy ground-glass opacities that correlated with disease severity, whereas the CT imaging of SN-CAP patients showed patchy high-density shadows. COVID-19 patients were classified into moderate, severe, and critically severe groups. The severe and critically severe groups had elevated levels of white blood cells (WBC), neutrophils, platelets, C-reaction protein (CRP), lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), troponin-I, creatinine, and blood urea nitrogen (BUN). However, they had decreased levels of lymphocytes, lymphocyte ratio, and albumin. Compared with the younger patients, the older COVID-19 individuals had more chronic diseases and significantly elevated levels of WBC, neutrophil, and CRP levels. Conclusion: SN-CAP showed more inflammatory reaction than COVID-19. Old people with chronic diseases are more susceptible to COVID-19 and have a high likelihood of developing severe and critically severe infection. Levels of WBC, lymphocytes, neutrophils, CRP, NLR, PLR, troponin-I, creatinine, and BUN are important indicators for severity grading in COVID-19.